Analisis Hubungan antar Parameter Pencemar Udara di Sekitar Pasar X menggunakan Metode Uji Korelasi pada Perangkat Lunak Minitab - Okik Hendriyanto Cahyonugroho; Tri Karisma Wardhani (Prosiding ESEC, 2023)
Market is a place to conduct transactions in the form of buying and selling and provide the needs of both goods and services. In addition, the market also has many roles from the role for producers to development. In planning the placement of the market, the thing that needs to be considered is air quality. Therefore, in this study, air quality measurements were taken directly at three points around the market. The results of air quality measurements will be carried out a correlation test using minitab software to determine the relationship between pollutant parameters. Air quality parameters measured are Sulfur Dioxide (SO2), Carbon Monoxide (CO), Nitrogen Dioxide (NO2), Oxidant (O3) accordingly, Non-methane Hydrocarbons, Total Solid Particulates, Lead (Pb), PM 10, and PM 2.5. The measurement results of these air quality parameters still meet the quality standards according to PP No. 22 of 2021. There are four parameters with the same results at each measurement point, so the correlation test was carried out on parameters with different levels, namely Sulfur Dioxide (SO2), Total Solid Particulate (TSP), PM10, PM2.5, and Lead (Pb). Based on the results of the correlation test, it is found that the parameters that correlate with each other are PM10, PM2.5, and Total Solid Particulate Matter (TSP) parameters. In addition, the parameters of Lead (Pb) and Sulfur Dioxide (SO2) are also correlated with each other but not with other parameters.